Identifikasi Bahaya pada Pekerjaan Oxy-Cutting di PT. Aziz Jaya Abadi Tuban - Rizqi Fajri Dhi'fansyah (The Indonesian Journal of Occupational Safety and Health, 2017)
Hazard identification is an effort to identify potential hazard that exist in the workplace. The aim of this study was identify hazards on Oxy-Cutting work in PT. Aziz Abadi Jaya Tuban. This study was a decriptive observational research with cross sectional design.Population of this study is 5 people consisting of 3 workers oxy - cutting, 1 welder superisor and 1 HSE Officer at PT. Aziz Jaya Abadi, Tuban. Samples from this study is the total population. Primary data were collected in the manner of observation and interviewing where as the secondary data obtained from the PT. Aziz Abadi Jaya Tuban profile and Oxy-Cutting Job Safety Analysis. The results showed that the hazards identified in Oxy-Cutting work on PT. Aziz Jaya Abadi Tuban includes damaged regulator, flashback arrestor not avaliable, leaking or torn hoses, the pressure is not balanced, smoking workers, the heat source due to the reaction of Oxy-Acetylene, dust, noise, and poor ergonomics. Company recommended to do risk control that doesnt exist yet to push the risk level with doingflashback arrestor installation and regulator replacement, noise measurement and environment measurement, provision of a fire extinguisher, tighten regulation of the use of personal protective equipment and conduct risk assessment at least once a year